Pengaruh Model Pembelajaran Mind Mapping Terhadap Hasil Belajar Siswa di SMPN 4 Bukittinggi - Chaliq Alwafi, Muhammad; Derta, Sarwo (Journal of Educational Management and Strategy, 2024)
This article is motivated by the problems that researchers found through observations at SMPN 4 Bukittinggi through interviews with teachers who teach ICT subjects, , where student learning outcomes are less than satisfactory, this is due to several factors including: student interest in the model used by the teacher when delivering lessons is very lacking, the model used is too monotonous, so that the lessons delivered by the teacher cannot be received well by students. The formulation of the problem in this study is whether there is an influence on the use of the Mind Mapping learning model on the learning outcomes of class VIII students in ICT subjects at SMPN 4 Bukittinggi. This study aims to determine whether there is an influence on the use of the Mind Mapping learning model on the learning outcomes of class VIII students in ICT subjects at SMPN 4 Bukittinggi. The type of research used is quantitative research in the form of Pre-Experiment. The population in this study were all students of class VIII A SMPN 4 Bukittinggi, the sample used the Purposive Sampling technique, namely a sampling process technique that is carried out based on certain characteristics that are considered to have a close relationship with the characteristics of the population that have been previously known. From 3 classes, 2 class representatives were obtained as samples to represent the population based on certain characteristics., Where class VIII A was obtained as the experimental class and class VIII B as the control class. Data obtained from the research results, the increase in learning outcomes of the experimental class was higher than the control class. Based on the results of the normality and homogeneity test of the test results from the two classes, it was obtained that the data of the two samples were normally distributed and homogeneous, so that the t-test could be used for hypothesis testing. According to the results of the research and discussion of the t-test calculation, tcount = 10.58 was obtained while the ttable value = 1.67 therefore tcount> ttable thus H0 was rejected and H1 was accepted, meaning that there was a difference between the learning outcomes of the experimental class and the control class. So it can be concluded that learning using the Mind Mapping learning model in the experimental class has more influence on student learning outcomes compared to students who are taught without using the Mind Mapping learning model. Abstrak Artikel ini dilatar belakangi oleh permasalahan yang peneliti temui melalui observasi di SMPN 4 Bukittinggi melalui wawancara bersama guru yang mengampu mata pelajaran TIK, dimana hasil belajar siswa kurang memuaskan, hal ini dikarenakan beberapa faktor diantaranya: ketertarikan siswa dengan model yang digunakan oleh guru disaat menyampaikan pelajaran sangat kurang, model yang digunakan terlalu monoton, sehingga pelajaran yang disampaikan guru tidak dapat diterima siswa dengan baik. Adapun rumusan masalah pada Artikel ini yaitu apakah terdapat pengaruh pada penggunaan model pembelajaran Mind Mapping terhadap hasil belajar siswa kelas VIII pada mata pelajaran TIK di SMPN 4 Bukittinggi. Artikel ini bertujuan untuk mengetahui apakah terdapat terdapat pengaruh pada penggunaan model pembelajaran Mind Mapping terhadap hasil belajar siswa kelas VIII pada mata pelajaran TIK di SMPN 4 Bukittinggi. Jenis Artikel yang digunakan adalah Artikel kuantitatif yang berbentuk Pre-Eksperiment. Populasi dalam Artikel ini adalah seluruh siswa kelas VIII A SMPN 4 Bukittinggi, Sampel yang digunakan teknik Purposive Sampling yaitu teknik proses pengambilan sampel yang dilakukan dengan didasarkan atas ciri-ciri tertentu yang dipandang mempunyai sangkut paut yang erat dengan ciri-ciri populasi yang sudah diketahui sebelumnya. Dari 3 kelas diperoleh perwakilan 2 kelas sebagai sampel untuk mewakili populasi berdasarkan ciri-ciri tertentu., Dimana didapat kelas VIII A sebagai kelas eksperimen dan kelas VIII B sebagai kelas kontrol. Data yang diperoleh dari hasil Artikel, peningkatan hasil belajar kelas eksperimen lebih tinggi dari pada kelas kontrol. Berdasarkan hasil uji normalitas dan homogenitas data hasil tes dari kedua kelas tersebut diperoleh bahwa data kedua sampel berdistribusi normal dan homogen, sehingga untuk pengujian hipotesis dapat digunakan uji t. menurut hasil Artikel dan pembahasan perhitungan uji t, diperoleh thitung = 10,58 sedangkan nilai ttabel = 1,67 oleh karena itu thitung > ttabel dengan demikian H0 ditolak dan H1 diterima, artinya terdapat perbedaan antara hasil belajar kelas eksperimen dengan kelas kontrol.  Jadi dapat disimpulkan bahwa pembelajaran dengan menggunakan model pembelajaran Mind Mapping pada kelas eksperimen lebih memberikan pengaruh terhadap hasil belajar siswa dibanding dengan siswa yang diajar tanpa menggunakan model pembelajaran Mind Mapping.